MEKANISME PARASITISME TRICHODERMA HARZIANUM TERHADAP FUSARIUM OXYSPORUM PADA SEMAI ACACIA MANGIUM - Susanti Tasik; Siti Muslimah Widyastuti; Harjono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Mechanism of parasitism of Trichoderma harzianum on Fusarium oxysporum on Acacia mangium seedlings. Fusarium oxysporum is one of the most important soil-borne fungi the causal agent of damping-off disease. Detailed information it needed to know how the pathogen can be inhibited by Trichoderma harzianum. The objective of this research was to investigate the inhibition mechanism of T. harzianum on F. oxysporum in vitro and in planta. Green Flourescent Protein (GFP) T. harzianum was used as biocontrol agent of F. oxysporum. An in vitro inhibition test of T. harzianum was performed using dual culture method. In the in planta inhibition tests, seedlings of A. mangium were applied with GFP T. harzianum two days before inoculation of F. oxysporum; GFP T. harzianum was simultaneously applied with F. oxysporum and GFP T. harzianum was applied two days after inoculation of F. oxysporum. The inhibition effect of T. harzianum GFP was observed at seven days incubation, indicated by attachment of T. harzianum to F. oxysporum hyphae. GFP T. harzianum hyphae covered the colonies of F. oxysporum at 12 days after incubation. The highest life percentage of A. mangium seedlings was found on the treatment of GFP T. harzianum two days before inoculation of F. oxysporum (82.22%), whereas the lowest life percentage was found on seedling applied with GFP T. harzianum two days after inoculation of F. oxysporum (64.44%).